EFEKTIVITAS MEDIA BOOKLET “4 ASUPAN KUNCI DI PERIODE EMAS ANAK” DALAM UPAYA PENCEGAHAN STUNTING - Retno Hastri Risqi Romdhani; Agustina Widayati; Riska Farasawati (Rena Cipta Mandiri, 2025)
Nutritional fulfillment in infants is a highlight and a topic still being debated in Indonesia. This happens because nutritional fulfillment is related to the incidence of stunting. The Ministry of Health and health services are intensively conducting socialization and evaluation of stunting issues (Syarif, N., 2022). One effort in preventing stunting is during the golden period of children aged 0-12 months when the child's brain is experiencing rapid development. The purpose of this study was to determine the effectiveness of using the booklet media 4 Key Intakes in the Golden Period of Children in stunting prevention efforts. This study used a quasi-experimental design. The population was 30 mothers with babies aged 0-6 months. The sampling technique used was purposive sampling. The analysis used a chi-square statistical test. The results of the study on the effectiveness of the booklet media before education on 4 key intakes in the golden period of children were 16 respondents with a percentage (53.4%) and an increase in knowledge after being given education was 18 respondents with a percentage (60%). The analysis using the Wilcoxon test showed a significance value of 0.000. There was a significant increase in maternal knowledge after the intervention using the booklet in Gading Village. It is hoped that this booklet can be a tool for health workers to increase knowledge among mothers of infants aged 0-6 months regarding the four key nutrients during their child's golden period.